Modal Sosial dan Integrasi Sosial: Asimilasi dan Akulturasi Budaya Masyarakat Multikultural di Polewali Mandar, Sulawesi Barat - Abd. Halim K.; Mahyuddin Mahyuddin (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2019)
This research aims to explain the role of the social capital of local community in integration process of inter-sociocultural. Discourse of multicultural society is important to be known because the difference of social community has a big potential to be a social disintegration. Nevertheless, the social life, which has different of culture, was not always occurred the disunion. Local wisdoms of community as social capital could facilitate an adhesive social so that they lived in social harmony. The type of this research is descriptive qualitative describing inter-ethnic social integration by taking place Wonomulyo, Polewali Mandar, West Sulawesi, one of provinces in Indonesia. The data collection techniques were observation, depth interview, and documentation. Withdrawal informants were done by purposive sampling. The theory used in this study was social capital by Robert Putnam and Pierre Bourdieu. This theory explained social capital by studying social habitus of local community. The results showed that social capital of local community had a role on processing integration of community that differ ethnic and culture. As a result, the ethnic groups integrated well was characterized by social relationships among ethnic groups remain in a stable state and bound in the integration of groups. Then, the equilibrium of groups created assimilation and acculturation of culture in the society. The ethnic groups cooperated each other in economy and social activity and there was no social conflict among them.